## iloveboys Group Title Simplify the following expression. 2x - 2y + 5z - 2x - y + 3z Answer 2x - 2y + 8z -3y + 8z x - 3y + 8z 3y + 8z 2 years ago 2 years ago

1. JamesJ

collect all the x terms; and all the y terms; and all the z terms. Then simplify

2. JamesJ

2x - 2y + 5z - 2x - y + 3z = (2x - 2x) + (-2y - y) + (5z + 3z) = ...

3. iloveboys

C?

4. JamesJ

(2x - 2x) + (-2y - y) + (5z + 3z) what is 2x - 2x equal to?

5. iloveboys

4x

6. JamesJ

No. 2x MINUS 2x = ...

7. iloveboys

its d wow.. well im an idiot. thanks james

8. JamesJ

No, it's not d. Figure it out explicitly: 2x - 2y + 5z - 2x - y + 3z = (2x - 2x) + (-2y - y) + (5z + 3z) = ...

9. iloveboys

im a bigger idiot.. lol. idontknow

10. JamesJ

2x - 2y + 5z - 2x - y + 3z = (2x - 2x) + (-2y - y) + (5z + 3z) = ... Figure out each piece in turn 2x - 2x = ... what? -2y - y = ... what? 5z + 3z = ... what?

11. iloveboys

x-3y+8z

12. iloveboys

oh

13. JamesJ

2x - 2x = 0 -2y - y = -3y 5z + 3z = 8z Hence 2x - 2y + 5z - 2x - y + 3z = (2x - 2x) + (-2y - y) + (5z + 3z) = ...what?

14. iloveboys

I dont know then. gosh

15. JamesJ

C'mon. This is now a reading exercise. 2x - 2x = 0 -2y - y = -3y 5z + 3z = 8z Hence 2x - 2y + 5z - 2x - y + 3z = (2x - 2x) + (-2y - y) + (5z + 3z) = 0 + what + what

16. iloveboys

3y+8z

17. iloveboys

witch i already said and u said no.. now im just confused.. hero! help

18. JamesJ

Given that: 2x - 2x = 0 -2y - y = -3y 5z + 3z = 8z it follows that ... 2x - 2y + 5z - 2x - y + 3z = (2x - 2x) + (-2y - y) + (5z + 3z) = 0 + -3y + 8z Hence the final answer is -3y + 8z.

19. JamesJ

That is 2x - 2y + 5z - 2x - y + 3z = -3y + 8z

20. iloveboys

because its negative.. omg. I would have failed my test already.lol. thanks james

21. JamesJ

I recommend you take a blank piece of paper. Write down the original expression and see if you obtain the answer again without looking at this web site. This is how I learnt this stuff. Repetition.